Analysis on Cryptographic Framework for IoE: Challenges and Issues - Baraneetharan, E. (Journal of ISMAC, 2022)
The Internet of Things (IoT) has been supplanted by the Internet of Everything (IoE) since lately. Cities, states/provinces, and the federal government all face the same problem of how to fulfill rising public expectations while dealing with shrinking or static resources. A growing chasm exists between public expectations and what governments are able to offer as a result of this problem. In addition, a wide range of additional concerns must be dealt with, at the federal, city/state/local, healthcare, military, and education levels as well. Since the advent of the Internet, nothing has been held as much promising for public sector executives as the Internet of Everything, which has the ability to bridge the gap between citizens’ expectations and what governments actually provide. The public sector has a unique chance to improve the quality of life for their citizens via the IoT. Type approval and cyber security methods, on the other hand, are critical for this new paradigm. Many traditional encryption algorithms fail in security and privacy in IoE which is not feasible for devices due to unawareness of the updated Trojan horse etc. The analysis of security and privacy issues for IoE domain is focused at various places such as home, city, government health center and more. In addition, it is at odds with the explanations offered by numerous IoE studies.